2002
DOI: 10.1111/1467-9450.00310
|View full text |Cite
|
Sign up to set email alerts
|

Age as a modifier of sexually aggressive attitudes in men

Abstract: Male attitudes and behaviours related to imagined sexual aggression were investigated in 99 Finnish men (mean age 24.3 years). Structural equation modelling suggested that imagined sexual aggression was directly predicted by hostile masculine ideologies and past antisocial acts, and indirectly by subject age (hostile masculinity decreased with age). For more detailed analyses of age effects on attitudes, the subjects were split into an older and a younger group. A small group of incarcerated rapists (n = 8; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…At the same time, among the youngest age groups, and males in particular, younger people have worse attitudes than their older counterparts. A series of international studies document that boys and young men are more likely than older men to endorse rape-supportive norms and to report a likelihood of committing rape (Aromaki, Haebich, & Lindman, 2002), whereas there are either no age-related differences among young females (Hutchinson, tess, gleckman, Hagans, & Reese, 1994) or gender differences that are greatest among younger individuals (Anderson et al, 2004). Among Australian youth aged 12 to 20, younger boys aged 12 to 14 showed higher support for violence-supportive attitudes than older males (NCP, 2001).…”
Section: Age and Developmentmentioning
confidence: 99%
“…At the same time, among the youngest age groups, and males in particular, younger people have worse attitudes than their older counterparts. A series of international studies document that boys and young men are more likely than older men to endorse rape-supportive norms and to report a likelihood of committing rape (Aromaki, Haebich, & Lindman, 2002), whereas there are either no age-related differences among young females (Hutchinson, tess, gleckman, Hagans, & Reese, 1994) or gender differences that are greatest among younger individuals (Anderson et al, 2004). Among Australian youth aged 12 to 20, younger boys aged 12 to 14 showed higher support for violence-supportive attitudes than older males (NCP, 2001).…”
Section: Age and Developmentmentioning
confidence: 99%
“…In addition, research findings shows that younger individuals below age 55 show improved attitudes toward beating (Carlson & Worden, 2005). Nonetheless, a series of international studies have shown that young males in particular are likely than older men to hold negative attitudes and endorse rape-supportive norms as well as reporting a likelihood of committing rape (Aromaki, Haebich, & Lindman, 2002).…”
Section: Factors Influencing Violencementioning
confidence: 99%
“…Also, in Knight and Sims-Knight’s (2003) unified model, an attitudinal factor termed “negative masculinity” loaded on to the “callous/unemotional traits” latent variable, which, as mentioned, strongly influenced aggressive sexual fantasies in community males. Similarly, using SEM, Aromäki et al (2002) found that the latent factor “hostile masculinity” (defined by hostile attitudes toward women, sexual dominance, and rape myths) had a direct influence on men’s “imagined sexual aggression,” a latent variable partially defined by coercive sexual fantasies.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, a number of studies have reported such findings using nonoffending males (Aromäki, Haebich, & Lindman, 2002; Bartels & Gannon, 2009; Dean & Malamuth, 1997; Greendlinger & Byrne, 1987; Plaud & Bigwood, 1997; Smeaton & Byrne, 1987; Zurbriggen & Yost, 2004). Also, in Knight and Sims-Knight’s (2003) unified model, an attitudinal factor termed “negative masculinity” loaded on to the “callous/unemotional traits” latent variable, which, as mentioned, strongly influenced aggressive sexual fantasies in community males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation